Cyclization/hydrolysis of 1, 5-enenitriles initiated by sulfonyl radicals in the aqueous phase in the presence of the I2/TBHP system. Issue 32 (25th July 2022) - Hu, Sen-Jie; Jiang, Li-Lin; Qiu, Hui; Luo, Chun-Mei; Guan, Yu-Tao; Li, Long; Dong, Youren; Lei, Ke-Wei; Wei, Wen-Ting
Abstract : A cyclization/hydrolysis of 1, 5-enenitriles for the synthesis of valuable pyrrolidine-2, 4-diones in the aqueous phase using I2 as the catalyst and tert -butyl hydroperoxide (TBHP) as the oxidant is reported. Abstract : A novel cyclization/hydrolysis of 1, 5-enenitriles for the synthesis of valuable pyrrolidine-2, 4-diones in the aqueous phase using I2 as the catalyst and tert -butyl hydroperoxide (TBHP) as the oxidant is reported. In the presence of the I2 /TBHP system, sulfonyl hydrazides produce sulfonyl radicals, which undergo radical addition, intramolecular cyclization, hydrogen abstraction, and hydrolysis to give the final products. The use of the inexpensive and environmentally friendly I2 /TBHP catalytic oxidation system in the aqueous phase makes it a benign and sustainable strategy.